Our Experience of Conscious Sedation as an Anaesthetic Technique in patients undergoing Automatic Implantable Cardioverter Defibrillator (Cardiovascular Journal, 2012)
Ten patients with life threatening ventricular arrhythmias who underwent placement of automatic cardioverter defibrillator ( AICD) under conscious sedation are reported. Our clinical experience, patient,s satisfaction, recovery profile and complications of the technique of conscious sedation is presented and discussed. Key words: Ventricular dysrhythmias; Autamatic implantable cardioverter defibrillator; Conscious sedation DOI: http://dx.doi.org/10.3329/cardio.v4i1.9388 Cardiovasc. J. 2011; 4(1): 42-45